PEMANFAATAN KATALIS BERBASIS KALIUM UNTUK MENDUKUNG EKONOMI SIRKULAR PADA INDUSTRI BIODIESEL - Giovani, Felix
Biodiesel is categorized as alternative fuel and is produced by the transesterification process of vegetable oil catalyzed by base catalyst, which also produce glycerol as by product. Catalyst normally used in the transesterification reaction is sodium-based catalyst such as NaOH and NaOCH3. But this process produces harmful waste to environment. This waste called glycerine pitch is produced within glycerol purification process. Glycerine pitch is a blackish-brown colored paste with a high COD rate, about 1,8–2 million mg/L, and categorized as hazardous waste. Hazardous waste management cost is quite considerable as the waste is harmful. Process modification of biodiesel production by changing the catalyst to potassium based could overcome this problem. This solution is based on the potential by product that may be produced. Glycerine pitch itself contains inorganic salts which is formed as the result of the acidbase reaction of the catalyst and the acid used in glycerol purification. As a result, sodiumbased salt is produced in the existing process. Sodium based salt’s price is not considerable enough to be extracted, but by exchanging the catalyst used to potassiumbased, then the high price potassium-based salt will be produced in exchange. This research proposes biodiesel production using potassium-based catalyst and will be compared to the existing process. Mass balance calculation is being done by using Aspen Plus V.10 as the simulator, continued by simple economic evaluation to determine the feasibility of the proposed process. GPM ratio of both processes are very sensitive to the price fluctuation of palm oil and biodiesel, which may occur. The proposed process has a GPM rate of 27,08%, which is higher than the existing process (GPM = 26,34%), so that the proposed process seems to be feasible to be implemented for industrial scale, by consideration that the proposed process is more profitable, also could overcome the environmental issue.